Decompression: a first-intention treatment for "large" non-syndromic odontogenic keratocysts - Muret Marjorie; Malthiéry Eve; Casenave Théo; Costes-Martineau Valérie; Torres Jacques-Henri (EDP Sciences, 2021)
Though odontogenic keratocysts (OKCs) are benign lesions, they have a high recurrence rate. Because of their aggressive behavior, they have been classified as tumors by the WHO until 2017. Main differential diagnoses are amelobastoma and dentigerous cyst. Anatomopathological examination can reach a final diagnosis. Several treatments have been proposed: curettage, resection, enucleation (alone or together with peripheral ostectomy) and decompression. Decompression aims to decrease the volume of the lesion of "large" OKCs, in order to prevent surgery-related fractures and to preserve the surrounding important anatomical structures such as the inferior alveolar nerve. It could lead to a complete regression. If not, secondary enucleation can be performed in better conditions: a reduced volume to remove, a thicker epithelium to detach, a lower risk to damage neighboring anatomic structures and a lower recurrence rate. Long-term follow-up however remains necessary. Nowadays, minimally invasive surgery prevails. And since OKC was returned into the odontogenic cysts group in the WHO classification, decompression should be considered as the first intention treatment. The purpose of this paper is to provide an update about OKC features and biological mechanisms, to review the different treatment options and to provide a step-by-step protocol for decompression.